IDDF2020-ABS-0189 Clinical analysis of LAPS in the treatment of hepatitis b virus-related hepatocellular carcinoma. (18th November 2020) - Chen, Zebin; Lei, Kai; Shen, Shunli; Peng, Baogang
Abstract : Background: The aim of the study is to assess the efficacy and safety of laparoscopic microwave ablation and portal vein ligation for staged hepatectomy (LAPS) in the treatment of hepatitis B virus-related hepatocellular carcinoma. Methods: Clinical data of patients with hepatitis B virus-related liver cancer who underwent LAPS or ALPPS surgery in the First Affiliated Hospital of Sun Yat-sen University from April 2013 to September 2019 were retrospectively analyzed. In the study, all patients signed informed consents and were approved by local ethics committees. Statistical analysis of data were performed by the SPSS 26.0. Results: 7 patients with HCC underwent LAPS, while 14 patients underwent ALPPS surgery during the same period. 42.9% of patients had a single tumor, and the median tumor diameter was 96 mm (range: 26–151 mm), the median preoperative FLR was 29.0% (range19.5%-38.8%). The severe morbidity rates of patients undergoing LAPS was lower than those receiving ALPPS after the first operation ( P =0.009). The median time to first passage of flatus of patients in the ALPPS group and LAPS group was 3d and 2d ( P =0.037) and the median time to out of bed was 4d and 2d ( P =0.040). 6 patients in the LAPS group completed the second stage operation, and 11 patients in the ALPPS group completed the second stage operation ( P =0.694). The median interval was 15 days in the LAPS group and 11 days in the ALPPS group ( P =0.006). The incidence of severe complications was 36.4% in the ALPSS group and 50.0% in the LAPS group after the second operation ( P =0.615). One patient in the ALPPS group died after the second operation. There was no difference in FLR growth rate, operative time and intraoperative loss between the two groups. Conclusions: LAPS has potential advantages over classical ALPPS in reducing postoperative liver failure and severe complications. LAPS may have the same effect in promoting the growth of FLR in patients with hepatitis B virus-related HCC, with a longer interval between the two operations.